Inclusive education management: A case study on planning and organizing at Syuhada Mosque primary school - Desmutri Hasanawati; Akbar Al Masjid; Elyas Djufri; Dinar Westri Andini (Kuras Institute, 2026)
Purpose – Inclusive education is a form of equitable education that seeks to provide equal educational opportunities and services for all pupils. The successful implementation of inclusive education is influenced by various aspects of school management, including planning and organizing. This study aims to describe the planning and organizing of inclusive education at Masjid Syuhada Primary School. Method – This study employed a qualitative approach with a case study design. The research was conducted at Masjid Syuhada Primary School, which implements inclusive education. Five participants were involved in the study, comprising the headteacher, teachers, and school staff who are involved in the management of inclusive education at the school. Data were collected through in-depth interviews and analyzed using thematic analysis, involving a process of coding, categorization, and theme development based on the approach proposed by Braun and Clarke. Findings – The thematic analysis identified two main themes: (1) assessment- and pupil-needs-based planning for inclusive education, and (2) organizing inclusive education through collaboration and role-sharing. In addition to these two main themes, an inclusive school culture emerged as a cross-cutting theme. The findings indicate that the management of inclusive education is implemented through planning based on assessment results and pupils’ needs, as well as organization supported by multi-stakeholder collaboration and a structured division of roles. An inclusive school culture serves as a key reinforcing factor underpinning the overall implementation process.